2016
DOI: 10.1177/1934578x1601100741
|View full text |Cite
|
Sign up to set email alerts
|

Phellinus igniarius: A Pharmacologically Active Polypore Mushroom

Abstract: Mushrooms have been widely used in traditional medicine for the treatment of various diseases. Today, their therapeutic value is scientifically studied and appreciated. Research indicates that polypores-a large group of fungi of the phylum Basdiomycota-exhibit antiviral, antimicrobial, anticancer, anti-allergic, anti-atherogenic, hypoglycemic, hepatoprotective and anti-inflammatory activities. Phellinus igniarius, a polypore mushroom, is one of the most used in traditional Asian medicine. Its potent anticancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Mushroom terpenes also show antiviral properties. A number of terpenes have been isolated from both medicinal and edible mushrooms, including G. lucidum , I. obliquus , P. igniarius , F. veltipes , H. erinaceus and P. eryngii ( Duru and Cayan, 2015 , Zapora et al, 2016 , Dasgupta and Acharya, 2019 ). To date, only terpenes from the mushroom genus Ganoderma have been investigated for anti-HIV properties.…”
Section: Discussionmentioning
confidence: 99%
“…Mushroom terpenes also show antiviral properties. A number of terpenes have been isolated from both medicinal and edible mushrooms, including G. lucidum , I. obliquus , P. igniarius , F. veltipes , H. erinaceus and P. eryngii ( Duru and Cayan, 2015 , Zapora et al, 2016 , Dasgupta and Acharya, 2019 ). To date, only terpenes from the mushroom genus Ganoderma have been investigated for anti-HIV properties.…”
Section: Discussionmentioning
confidence: 99%
“…The water extract also showed good anti-FIV-RT activity. It has been reported that some proteins and polysaccharides extracted from mushrooms showed antiviral potential [ 12 , 24 , 25 , 27 , 29 , 31 , 32 , 35 , 37 , 38 ] ( Table-2 ). Thus, the experimental design to obtain the anti-FIV compounds (e.g., type of inhibitor, solvent used, and purification method) should be taken into account in further studies and clinical applications.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, existing chemical and biological drugs for cancers and diabetes have many drawbacks, such as large side effects and high prices [ 4 , 5 , 6 ]. Therefore, natural products that possess hypoglycemic, anti-oxidation, and anticancer properties is of great significance and drew the researchers’ attention [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%